Multitasking in Embedded System Designs - Mavrevski, Radoslav; Traykov, Metodi; Trenchev, Iavn (International Journal of Online and Biomedical Engineering (iJOE), 2019)
It is common knowledge in Information Technology (IT) that an embedded system is based on microprocessor and is built to control a function or a range of functions. Although, it is not designed to be programmed by the end user in the same way that a PC is, it is designed to perform one particular task with choices and different options [1-5]. Multitasking is a method by which multiple tasks, also known as processes, share common processing resources, such as CPU. The main aim of this paper is analysis of the design of the embedded systems and a focus on mid-level abstractions for concurrent programs.